Liquefaction Phenomena Induced by the 26 November 2019, Mw = 6.4 Durrës (Albania) Earthquake and Liquefaction Susceptibility Assessment in the Affected Area - Spyridon Mavroulis; Efthymios Lekkas; Panayotis Carydis (Geosciences, 2021)
On 26 November 2019, an Mw = 6.4 earthquake struck the central-western part of Albania. Its impact comprises secondary earthquake environmental effects (EEE) and severe building damage within the Periadriatic and the Tirana Depressions. EEE comprised mainly liquefaction phenomena in coastal, riverine, and lagoonal sites of the earthquake-affected area. From the evaluation of all available earthquake-related data, it is concluded that liquefaction sites are not randomly distributed within the affected area but are structurally and lithologically controlled. The affected areas are distributed within NW–SE striking zones formed in graben-like syncline areas with NW–SE trending fold axes. These graben-like areas are bounded by NW–SE striking marginal thrust faults and are filled with geological formations of Neogene to Quaternary age. These NW–SE striking zones and structures coincide with the NW–SE striking seismogenic thrust fault of the November 2019 earthquake as it is derived from the provided fault plane solutions. An approach for liquefaction susceptibility assessment is applied based on geological and seismological data and on liquefaction inventory. From the comparison of the compiled liquefaction inventory and the susceptibility maps, it is concluded that the majority of the observed liquefaction has been generated in very high and high susceptible areas.